Social innovation and challenges in youth-based sport practices: An analysis of state-led programs - Açikgöz, S.; Haudenhuyse, R.; Tinaz, C. (Springer International Publishing, 2021)
'Project' models offer an innovative alternative for sports for development (SFD) programs; however, such models can also bring uncertainty for organizations outside the western world, which can grapple with problems of incapacity. This chapter reveals the implementation process of a sports-based youth project in Turkey, through interviews with project stakeholders such as coordinators and trainers. A traditional public administration approach is used to discuss the position of the organizations, and in-project practices are compared with emerging innovation concepts (i.e. design thinking, servant leadership) in SFD literature. The findings highlight how certain organizations with a lack of expertise encounter fundamental problems, preventing the execution of an innovative and socially inclusive program. The chapter concludes with suggestions for policy makers and practitioners who conduct SFD programs in challenging organizational environments. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2021.